2017
DOI: 10.1007/s40519-017-0453-2
|View full text |Cite
|
Sign up to set email alerts
|

Is poor sleep associated with obesity in older adults? A narrative review of the literature

Abstract: Level V, narrative review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 78 publications
0
14
0
1
Order By: Relevance
“…In parallel, experimental findings suggested that sleep deprivation modulates EFs in healthy samples, although findings are not entirely consistent. Couyoumdjian et al (2010) and Gorgoni et al (2014) found that total sleep deprivation depletes inhibitory capacities, whilst a recent study from our group suggested that partial sleep deprivation might have a slight beneficial effect on non-inhibitory switching capacities as assessed in task switching paradigm (see below), but no effects on inhibitory capacities (Ballesio et al, 2018). Taken together, these findings may suggest that one mechanism by which disrupted sleep patterns may increase food intake is via changes of EFs (Lundahl & Nelson, 2015).…”
Section: Introductionmentioning
confidence: 75%
See 3 more Smart Citations
“…In parallel, experimental findings suggested that sleep deprivation modulates EFs in healthy samples, although findings are not entirely consistent. Couyoumdjian et al (2010) and Gorgoni et al (2014) found that total sleep deprivation depletes inhibitory capacities, whilst a recent study from our group suggested that partial sleep deprivation might have a slight beneficial effect on non-inhibitory switching capacities as assessed in task switching paradigm (see below), but no effects on inhibitory capacities (Ballesio et al, 2018). Taken together, these findings may suggest that one mechanism by which disrupted sleep patterns may increase food intake is via changes of EFs (Lundahl & Nelson, 2015).…”
Section: Introductionmentioning
confidence: 75%
“…Throughout the entire duration of the study, sleep was measured both subjectively, using sleep diaries, and objectively, through a portable electronic device called Zeo (Inc., Newton, MA) (Cellini et al, 2015), which was used to monitor the compliance to the sleep deprivation instructions as previously reported (Lombardo et al, 2020;Ballesio et al, 2018).…”
Section: Sleep Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Watching television (TV) is also a lifestyle behavior associated with obesity, due to the lack of movement involved, the snacking related to TV viewing, or the combination of both [12,13]. Sleep has been linked to energy metabolism and body mass index (BMI), with recent studies suggesting that too much or too little sleep is detrimental and may be associated with obesity [14][15][16]. Furthermore, sleep, physical activity, and screen time have been found to be concurrent in some cases, but in others their correlation was moderate to small and their associations were not statistically significant [17][18][19].…”
Section: Introductionmentioning
confidence: 99%